Health-preserving physical culture and wellness competences as an important condition for ensuring and spreading a high level of public health (methodological aspects) - A. M. Hurieieva; V. V. Prykhodko; O. V. Sheviakov; S. A. Chernihivska; V. M. Vilianskyi; O. O. Cherepok (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
WHO indicates that the purpose of actions aimed at strengthening public health protection is to ensure conditions under which people can remain healthy, able to strengthen health and well-being, and prevent deterioration of health. However, in the basic documents, there is no place for health-preserving physical culture and health-improving competencies of a person in the system of general efforts.